MEDIA KARTU BACA UNTUK PEMBELAJARAN BERDIFERENSIASI: SUATU UPAYA UNTUK MENGEMBANGKAN KETERAMPILAN MEMBACA PADA SISWA SD AL-FATAH 1 AMBON - Ainia Ely; Lutma Ranta Allolinggi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to examine differences in students’ reading skills between those who received instruction using word cards integrated with differentiated learning and those in the control group. A quantitative approach with a quasi-experimental design was employed. Reading skill data were collected through a test and analyzed using descriptive statistics and an independent-samples t-test. The results showed that the experimental group achieved a mean score of 78.02, compared with 69.87 in the control group. The statistical analysis revealed a significant difference between the two groups, with t(55) = 3.261 and p = 0.002. The Cohen’s d value of 0.864 indicated a large effect size. These findings suggest that integrating word cards with differentiated learning resulted in higher reading skill outcomes than those achieved by students in the control group.